Depression, anxiety and stress among dental students during COVID-19 pandemic and distance learning - Limeira, Francisco Ivison Rodrigues; Cruz, Poliana Farias da; Andrade, Amanda Ribeiro da Costa; Guiomarino Neto, Armando Baia; Arantes, Diandra Costa (Revista da ABENO, 2022)
This study aimed to measure the levels of depression, anxiety and stress among dental students during the COVID-19 pandemic and distance learning. This cross-sectional questionnaire-based survey was conducted at a Brazilian school of Dentistry, between July and August, 2020. The participants were surveyed using the adapted and validated version of Depression, Anxiety, and Stress Scale (DASS21) questionnaire. The Fisher's exact test and bivariate logistic regression analysis were performed to analyze the data, using SPSS software. A total of 120 dental students (response rate of 87.60%) participated in the study; 75.8% of them were female and the mean age was 23.35 years old (± 6.07). Most students were single (85%), studied full time (68.3%) and had no employment (70.8%). Some level of depression, anxiety and stress was observed in 64.2%, 67.5% and 61.7% of the students, respectively. The severity of the depression, the anxiety and the stress was significantly associated (p < 0.05) with the student’s gender, fear of contracting COVID-19 and with the condition of having a family member who has already had COVID-19. Female students, students who were fear of contracting COVID-19 and who had a familiar or a friend diagnosed with COVID-19 presented more chances of developing a high level of depression, anxiety or stress. We concluded that dental students had high levels of depression, anxiety and stress during the COVID-19 pandemic and distance learning. This study suggests that the mental health of dental students nshould be carefully monitored during the COVID-19 pandemic